Immunopathogenesis of Sarcoidosis - Vagts, Christen; Ascoli, Christian; Jacobson, Jeffrey R. (Seminars in Respiratory and Critical Care Medicine, 2025)
Sarcoidosis is a granulomatous disease of unknown cause, triggered by an unidentified antigen. Although classically considered a T cell–mediated disorder with an IFN-γ signature driven by Th1, Th17, and Th17.1 cells, its pathogenesis reflects dysregulated crosstalk between innate and adaptive immunity. Granulomas form through macrophage differentiation at the core, fueled by aberrantly programmed monocytes and sustained by persistent antigen presentation to T cells. Hyperactive macrophages drive excessive peripheral cell recruitment, while dysregulated T cell responses promote T cell expansion, impaired effector regulation, and eventual exhaustion. Deficient regulatory pathways fail to counterbalance this activation, creating a perpetuating inflammatory loop that underlies disease persistence and fibrotic progression. This review integrates up-to-date transcriptomic and biological data to define the cellular and molecular mechanisms that initiate, sustain, and dysregulate immune responses in sarcoidosis.
Keywords: sarcoidosis; immunopathogenesis; granulomatous inflammation; innate immunity; adaptive immunity; interstitial lung disease